Impact of creatine supplementation in combination with resistance training on lean mass in the elderly. Issue 4 (18th January 2016) - Pinto, Camila Lemos; Botelho, Patrícia Borges; Carneiro, Juliana Alves; Mota, João Felipe
Abstract: Background: Human ageing is a process characterized by loss of muscle mass, strength, and bone mass. We aimed to examine the efficacy of low‐dose creatine supplementation associated with resistance training on lean mass, strength, and bone mass in the elderly. Methods: This was a 12‐week, parallel‐group, double‐blind, randomized, placebo‐controlled trial. The individuals were randomly allocated into one of the following groups: placebo plus resistance training (PL + RT) and creatine supplementation plus resistance training (CR + RT) . The participants were assessed at baseline and after 12 weeks. The primary outcomes were lean mass and strength, assessed by dual energy X‐ray absorptiometry (DXA) and ten‐repetition maximal tests (10 RM), respectively. Secondary outcomes included the lumbar spine, right and left femoral neck, both femur and whole body bone mineral density (BMD), and whole body bone mineral content (BMC), assessed by DXA. Results: The CR + RT group had superior gains in lean mass when compared with the PL + RT group ( P = 0.02). Changes in the 10 RM tests in bench press and leg press exercises, body composition, BMD, and BMC of all assessed sites did not significantly differ between the groups ( P > 0.05). Conclusions: Twelve weeks of low‐dose creatine supplementation associated with resistance training resulted in increases in lean mass in the elderly.